Importance of Cobalt-60 Dose Rate and Biologically Effective Dose on Local Control for Intracranial Meningiomas Treated With Stereotactic Radiosurgery. Issue 1 (January 2022) - Huo, Michael; Rose, Melanie; van Prooijen, Monique; Cusimano, Michael D.; Laperriere, Normand; Heaton, Robert; Gentili, Fred; Payne, David; Shultz, David B.; Kongkham, Paul; Kalia, Suneil K.; Schwartz, Michael; et al.
Abstract : BACKGROUND: Radiosurgery dose rate and biologically effective dose (BED) are associated with outcomes after stereotactic radiosurgery (SRS) for functional neurosurgical conditions and some benign tumors. It is not known if these factors affect the efficacy of SRS for meningioma. OBJECTIVE: To determine the association between cobalt-60 dose rate and BED on outcomes in patients with meningioma treated with SRS. METHODS: A single-institution cohort of 336 patients treated between 2005 and 2018 with cobalt-based SRS for 414 separate meningioma lesions was assembled. BED was calculated using an SRS-specific monoexponential model accounting for treatment time per lesion, assuming α/β = 2.47 Gy. Cumulative incidences of local failure (LF) were reported after considering the competing risk of death, on a per-lesion basis. Multivariable analysis of LF was performed using a proportional hazards model. RESULTS: The most common SRS dose was 12 Gy (n = 227); 140 lesions received 14 Gy. Five-year LF was 15.6% (95% confidence interval 10.4-21.9) and 4.3% (1.4-9.8) in patients who had a dose rate of <2.95 and ≥2.95 Gy/min, respectively ( P = .0375). Among 354 grade I or unresected lesions treated with SRS, BED >50 Gy2.47 was associated with a lower incidence of LF ( P = .0030). Each 1 Gy/min increase in dose rate was associated with an adjusted hazard ratio of 0.53 (95% confidence interval, 0.29-0.97, P = .041) for LF. Prescription dose >12 Gy was not associated with a lower incidence of LF. CONCLUSION: Patients with meningiomas treated with lower dose rates experienced a higher incidence of LF than those treated with higher dose rates.